THE EFFECTIVENESS OF STUDENTS’ CREATIVE WRITING ABILITY THROUGH COLLABORATIVE CLUSTERING TECHNIQUE AND ICT (INFORMATION AND COMMUNICATIONS TECHNOLOGY) IN THE SECOND SEMESTER OF IAIN KEDIRI - Nafi'yah, Siti; Ika Misela, Jenny (JURNAL KOULUTUS, 2019)
The purpose of this study is to observe the effectiveness of learning to develop writing through Clustering Technique and ICT, ICT used is using Edmodo.so this can reduce teacher solutions to overcome problems encountered in teaching and learning activities in writing text writing. This type of research is quantitative, namely pre-experiment. The techniques used in this study are observation, interviews, pre-test, treatment then post-test. Data from this study are information from students and teachers about the teaching techniques used by lecturers when teaching in class. The subjects of this study were English class F students in semester 2 of 2018/2019 school year. This study uses data selection, shows data, and writes conclusions and verification of data analysis results. The findings in this study indicate that the use of clustering techniques and ICT in learning writing is effective. to analyze all data using the formula of Anas Sudijono (P.81). Analysis of the writings is based on Brown's theory (2007). This is indicated by the results of the pre test 71% of students who derived the score above the minimum Mastery Criterion- Kriteria kesan Minimal (KKM) . meanwhile the other 25% students were below that criterion. the lowest achievement gained score 69, the highest score is 86, based on the postest can be know 4 students or 11% get the low score from KKM but 31 students or 89% get the high score from KKM, it will be known that all students 0r 35 students get the high score from KKM. In conclusion the results of the post test are better than the results of the pre test.Keywords: writing, clustering technique, ICT (Information and communications technology)